Trends in the Disease Burden and Risk Factors of Women’s Cancers in China From 1990 to 2019 - Wei Ning; Wei Ning; Jinnan Liu; Yongbo Lu; Bin Zhu; Wei-Hong Zhang; Ying Mao (International Journal of Public Health)
ObjectivesTo examine age-specific trends and risk factors in the burden of women’s cancers (WCs) in China from 1990 to 2019 to inform strategies.MethodsData were sourced from the Global Burden of Disease 2019 and World Population Prospects 2019. Time trends, age differences, and key factors for breast, cervical, and ovarian cancers (BC, CC, and OC) were analyzed based on age-standardized incidence rate (ASIR) and disability-adjusted life years (DALYs) rate.ResultsASIRs for BC and CC increased over the study period, with a slower growth rate for CC after 2005, likely due to targeted HPV prevention. OC showed the highest ASIR and DALY increases, indicating a growing concern. Peak ASIR for BC and CC was in women aged 50–55, while OC showed a higher burden in women aged 70–79. Lower DALYs in women born after 1985 suggest improved healthcare access.ConclusionThis study highlights significant trends in cancer burden among Chinese women, driven by age and reproductive health policies. Future efforts should enhance screening, health literacy, and age-targeted risk reduction for specific cancer types.